Pelatihan Terapi Genggam Jari dalam Mengatasi Nyeri Pasca Operasi - Mulyanti Roberto Muliantino; Reni Prima Gusty; Ovitra Mulyawati; Fadhil Akbar; Vivi Ramadhani; Rani Afdila Pratiwi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2022)
The pain was the main problem in post-surgery patients and sometimes resulted in activity limitations. One non-pharmacological therapy was finger gripping therapy which can be an option for overcoming post-operative pain. The activity aimed to increase the knowledge and skills of patients under surgery in treating their pain using the finger-gripping therapy method. This training was carried out ten on post-operative patients from the surgery recovery room in hospitals in Padang. We used PowerPoint presentations, leaflets, and simulation videos in this training. Pre-test and post-test were used in the evaluation stage. The results showed that there was increased knowledge of patients after attending finger grip therapy training. The patient’s pain level decreased after practising finger gripping therapy. The training and education programme effectively improved the knowledge and skills of patients in managing their pain independently. Continuing education can be an effort to enhance the self-management of post-operative patients.